3-D automatic setup of ERT (electrical resistivity tomography) system - Łukowski, J.; Pidvirnyy, O. (2011)
The paper presents results of work on 3-D the surface scanning system using ERT method. The construction of automatic laboratory system for imaging of the internal structure and heterogeneity of concrete structures by ERT method, using a multi-electrode surface scanner of electrical conductivity of concrete objects will be used to model tests and actual concrete structures by multi-point and non-contact method for measuring the electrical conductivity of concrete structures, in particular.